Tunable passively Q-switched thulium doped fluoride fibre (TDFF) laser using reduced graphene oxide-silver (rGO-Ag) as saturable absorber - Ahmada, H.; Azmy, N. F.; Reduan, S. A.; Reduan, S. A.; Yusoff, N.; Bayang, L.; Zulkifli, Mohd Zamani; Thambiratnam, K. (Taylor & Francis, 2020)
A tunable, passively Q-switched thulium doped fluoride fibre (TDFF) laser using a reduced-graphene oxide-silver (rGO-Ag) thin film as a saturable absorber (SA) for S band operation is proposed and its efficacy demonstrated. Over a pump power range of 91.4 mW up to 158.6 mW, passively generated Q-switched pulses are observed with repetition rates from 20 to 34.5 kHz and pulse widths from 3.1 to 7.1 µs. The highest pulse energy observed is 101.2 nJ with a signal to noise ratio of ∼ 42 dB. The proposed laser has a tuning range ∼ 52 nm from 1458 to 1510 nm with a tunable bandpass filter (TBPF) introduced into the cavity.